Can conservation agriculture increase soil carbon sequestration? A modelling approach - Valkama, Elena; Kunypiyaeva, Gulya; Zhapayev, Rauan; Karabayev, Muratbek; Zhusupbekov, Erbol; Perego, Alessia; Schillaci, Calogero; Sacco, Dario; Moretti, Barbara; Grignani, Carlo; Acutis, Marco (Geoderma, 2020)
[Display omitted] •SOC changes were simulated in three sites with contrasting soils and climates.•Conventional tillage (Conv − R and Conv + R) led to SOC decline in all sites.•No-tillage (NT) could slightly increase the annual SOC in all sites.•C sequestration rate of 0.4% yr−1 is achievable under conservation agriculture (CA)•Cover crops (in CA + CC) would allow a higher annual sequestration rate. Conservation agriculture (CA) involves complex and interactive processes that ultimately determine soil carbon (C) storage, making it difficult to identify clear patterns. To solve these problems, we used the ARMOSA process-based crop model to simulate the contribution of different CA components (minimum soil disturbance, permanent soil cover with crop residues and/or cover crops, and diversification of plant species) to soil organic carbon stock (SOC) sequestration at 0–30 cm soil depth and to compare it with SOC evolution under conventional agricultural practices. We simulated SOC changes in three sites located in Central Asia (Almalybak, Kazakhstan), Northern Europe (Jokioinen, Finland) and Southern Europe (Lombriasco, Italy), which have contrasting soils, organic carbon contents, climates, crops and management intensity. Simulations were carried out for the current climate conditions (1998–2017) and future climatic scenario (period 2020–2040, scenario Representative Concentration Pathway RCP 6.0). Five cropping systems were simulated: conventional systems under ploughing with monoculture and residues removed (Conv − R) or residues retained (Conv + R); no-tillage (NT); CA and CA with a cover crop, Italian ryegrass (CA + CC). In Conv − R, Conv + R and NT, the simulated monocultures were spring barley in Almalybak and Jokioinen, and maize in Lombriasco. In all sites, conventional systems led to SOC decline of 170–1000 kg ha−1 yr−1, whereas NT can slightly increase the SOC. CA and CA + CC have the potential for a C sequestration rate of 0.4% yr−1 or higher in Almalybak and Jokioinen, and thus, the objective of the “4 per 1000” initiative can be achieved. Cover crops (in CA + CC) have a potential for a C sequestration rate of 0.36–0.5% yr−1 in Southern Finland and in Southern Kazakhstan under the current climate conditions, and their role will grow in importance in the future. Even if in Lombriasco it was not possible to meet the “4 per 1000”, there was a SOC increase under CA and CA + CC. In conclusion, the simultaneous adoption of all the three CA principles becomes more and more relevant in order to accomplish soil C sequestration as an urgent action to combat climate change and to ensure food security.